Hydrochemical characteristics and water quality indices‐based assessment of River Kali for agricultural irrigation in northern India. (10th October 2021) - Singh, Gaurav; Patel, Neelam; Jindal, Tanu; Ranjan, Manju Rawat; Pal, Sumit; Ahirwal, Jitendra; Dubey, Swatantra Kumar
Abstract: High‐quality water is required to produce a greater crop yield. River water is a major source of irrigation; however, in several densely populated countries, it is severely polluted due to anthropogenic activities. We aim to assess the Kali River water quality from 17 sampling stations using hydrochemical characterization in western Uttar Pradesh during the pre‐ and post‐monsoon seasons. The suitability of river water quality for agricultural irrigation was determined by water quality indices such as sodium adsorption ratio (SAR), sodium percentage (Na%), residual sodium carbonate (RSC), permeability index (PI), magnesium ratio (MR), and Kelley's index (KI). Results of the study showed that water quality in terms of pH, electrical conductivity, total dissolved solids, Cl −, SAR, and MR is moderately suitable for agricultural irrigation. However, only 64.7% (NO3 − N), 88.2% (HCO3 − ), and 70.6% (B) samples in pre‐monsoon and 70.6% (NO3 − N), 100% (HCO3 − ), and 64.7% (B) samples in post‐monsoon were acceptable for irrigation. In addition, 94.1%, 23.5%, and 70.6% of samples in pre‐monsoon and 82.4%, 17.6%, and 23.5% of samples in post‐monsoon analysed for Na%, RSC, PI, and KI, respectively, were found suitable for irrigation. The analysis of selected water quality parameters and water quality indices shows that Kali River water is polluted at the downstream side, and its suitability for agricultural irrigation varies with the season. Abstract: L'eau de haute qualité est nécessaire pour augmenter le rendement des cultures. L'eau des rivières est une source majeure d'irrigation, cependant, dans plusieurs pays densément peuplés, elle est sévèrement polluée en raison des activités anthropiques. Nous visons à évaluer la qualité de l'eau de la rivière Kali à partir de 17 stations de prélèvement en utilisant la caractérisation hydro‐chimique dans l'ouest de l'Uttar Pradesh pendant les saisons précédant et suivant la mousson. La pertinence de la qualité de l'eau des rivières pour l'irrigation agricole a été déterminée par des indices de qualité de l'eau tels que le taux d'adsorption du sodium, le pourcentage de sodium, le carbonate de sodium résiduel, l'indice de perméabilité, le taux de magnésium et l'indice de Kelley. Les résultats de l'étude ont montré que la qualité de l'eau en termes de pH, EC, TDS, Cl‐, SAR et MR est modérément adaptée pour l'irrigation agricole. Cependant, seuls 64, 7% (NO3‐N), 88, 2% (HCO3‐), et 70, 6% (B) des échantillons pré‐mousson et 70, 6% (NO3‐N), 100% (HCO3‐), et 64, 7% (B) des échantillons post‐mousson étaient acceptables pour l'irrigation. En outre, 94, 1%, 23, 5% et 70, 6% des échantillons prélevés avant la mousson et 82, 4%, 17, 6% et 23, 5% des échantillons prélevés après la mousson ont été analysés respectivement pour Na%, RSC, PI et KI. L'analyse des paramètres de qualité de l'eau sélectionnés et des indices de qualité de l'eau montre que l'eau de la rivière Kali est polluée en aval et que son aptitude à l'irrigation agricole varie avec la saison.